The integration of Christian spirituality into evangelical Christian education in the local South African church - Smallbones, Jacqueline L. (Durban-Westville University, 1994)
The purpose of this thesis, an integration of Christian spirituality into Evangelical Christian education, has required that both these disciplines be explored and discussed. Christian spirituality has been limited to a discussion of Evangelical and Anglo-Catholic spirituality, and has included a discussion of the commonalities between these two traditions. Since both are extremely vast, this thesis does not cover all the varieties within each tradition itself. The focus has been for a general understanding of spirituality in order to integrate it with education in the local South African church context. Christian education has been explored from the perspective of education within the local church, particularly of adults. I do not consider the role of the school, nor do I cover the education of children and youth. These were necessary limitations to my topic. The discussion of Christian education is taken from a broad perspective, not just an evangelical due to the sparsity of literature on evangelical education. Based on this research, suggested guidelines for the integration of Christian spirituality into Christian education in the local South African evangelical church are given. This forms the basis of part III of this thesis. This section begins with a discussion of the points of contact between these two traditions, which forms the direction that the final chapter takes, giving some specific guidelines. These guidelines focus on the Evangelical emphases with the centrality of scripture being crucial. The general conclusion of this thesis is that the task of integrating Christian spirituality into Christian education should not be that difficult since there is already much that is common between them.
free